2012
DOI: 10.1007/s12041-012-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of flowering time in bread wheat Triticum aestivum: complementary interaction between vernalization-insensitive and photoperiod-insensitive mutations imparts very early flowering habit to spring wheat

Abstract: Time to flowering in the winter growth habit bread wheat is dependent on vernalization (exposure to cold conditions) and exposure to long days (photoperiod). Dominant Vrn-1 (Vrn-A1, Vrn-B1 and Vrn-D1) alleles are associated with vernalization independent spring growth habit. The semidominant Ppd-D1a mutation confers photoperiod-insensitivity or rapid flowering in wheat under short day and long day conditions. The objective of this study was to reveal the nature of interaction between Vrn-1 and Ppd-D1a mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 60 publications
5
18
0
2
Order By: Relevance
“…It was reported that wheat genotypes with all three dominant alleles of Vrn-1 genes (Vrn-A1, Vrn-B1, and Vrn-D1) head quite early compared to mono-or di-dominant gene combinations [28]. Similar information was also reported by various authors [5,9,[57][58][59]. From the results of the above-mentioned studies, it was shown which combinations of alleles perform better than others.…”
Section: The Interaction Of Vrn and Ppd Alleles And Its Impact On Flosupporting
confidence: 74%
See 4 more Smart Citations
“…It was reported that wheat genotypes with all three dominant alleles of Vrn-1 genes (Vrn-A1, Vrn-B1, and Vrn-D1) head quite early compared to mono-or di-dominant gene combinations [28]. Similar information was also reported by various authors [5,9,[57][58][59]. From the results of the above-mentioned studies, it was shown which combinations of alleles perform better than others.…”
Section: The Interaction Of Vrn and Ppd Alleles And Its Impact On Flosupporting
confidence: 74%
“…An epistatic interaction between the Vrn-A1 and Vrn-D1 active alleles was demonstrated in a study [9]. The same study confirmed an additive/complementary interaction for flowering time between the photoperiod-insensitive Ppd-D1a allele and the Vrn-1 active alleles [57,60].…”
Section: The Interaction Of Vrn and Ppd Alleles And Its Impact On Flosupporting
confidence: 53%
See 3 more Smart Citations